Labour market segmentation and the EU reform agenda: developing alternatives to the mainstream - Rubery, Jill; Piasna, Agnieszka (Brussels, 2016)
"European employment regulation has been repeatedly identified by policymakers as too stringent resulting in policy recommendations aimed at a more flexible labour market. This diagnosis has been reaffirmed, particularly by international policymakers, in the post-2008 economic and jobs crisis with high employment protection regarded as harmful for employment, responsible for boosting precarious jobs and likely to result in social costs including unemployment. The labour market reforms pushed by the European Commission after 2010 targeted reducing employment protection legislation (EPL) with the dual expectation that they will revive “job creation in sclerotic labour markets while tackling segmentation and adjustment at the same time” (European Commission 2012, 4).